The bidirectional relationship between host physiology and microbiota and health benefits of probiotics: A review. (September 2019) - Cheng, Dan; Song, Jingzheng; Xie, Meizhen; Song, Danfeng
Abstract: Background: Probiotic consumption has dramatically grown with most products claim of gastrointestinal health and immune support. The beneficial potential of probiotic has gradually expanded to areas such as mood improvement, metabolism homeostasis and vaginal health according to scientific research advances. The positive research results provide novel and promising insight into preventing and even therapeutic methods for various human morbidity by probiotic. Scope and approach: This review summarized the bidirectional relationship between the host physiology and microbiota from various animal experiments and clinical studies reported in peer-reviewed journal articles. Then the study summarized the benefits that probiotic confer to the host physiology. As a kind of food supplement, application precautions and formula suggestions were also provided for futuristic research and product development. Key Findings and Conclusions: Microbial ecosystem has a symbiotic relationship with host. The alteration in the host physiology and shift in the microbial composition in the hosts can positively or negatively impact each other. The clear and thorough comprehension of the complexity of microbiota–host crosstalk is significant for the development of probiotic intervention. Probiotic may confer various benefits ranging from traditional immune support, gastrointestinal heath even to disease control as sepsis prevention. Probiotic may function in the host mainly through competing with deleterious bacteria, beneficial metabolites and maintaining the homeostasis of gut, and new mechanisms are being discovered each year. The failed clinical study and negative results of probiotic treatment may propose the customized probiotic design for treatment. For probiotic supplement products in the market, upgrading are strongly suggested from aspects of formula innovation and clinically referred probiotic dosage. Highlights: Host physiology and microbiota are highly associated and can impact each other by a bidirectional manner. Probiotic can positively impact host physiology and even treat various diseases in different mechanisms. Probiotic supplement formula should be uniquely designed for efficient and accurate treatment.